DTA and TGA study of MeSo4 (Me = Fe, Co, Ni) dissociation in the presence of coke - Boyanov B.S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
MeSO4 (Me = Fe, Co, Ni) dissociation is investigated in order to estimate the effect of temperature, time and presence of coke as reducer on the degree and mechanism of dissociation. It is proved that the presence of coke decreases the dissociation temperature considerably and increases the degree of MeSO4 dissociation. Based on the obtained experimental data, a mechanism of the processes is proposed. The obtained results can be used in the industrial production of non-ferrous metals for explaining the processes that take place in the reduction of zinc and lead cakes in order to achieve favorable environmental, technical and economic results.